Welding Connection Strenght of Aluminium 1100 with Current Variations at Metal Inert Gas (MIG) Welding Process - Krishna Muku, I Dewa Made (Jurnal Energi Dan Manufaktur; Vol 3, No.1 April 2009)
In order to design of machine or building constructions use of welding connection, there are many factors should beconsidered such as skill, knowledge about welding procedures and material characteristics. One parameter of weldingprocedures influencing mechanical characteristic of weld metal is welding current. In this study, strength of aluminium 1100welding connection due to electric current variations at metal inert gas welding process was investigated. Spesimen to beused was standard ASTM E 8. Electric current variations to be set were 150 A, 165 A, 180 A, 195 A and 210 A, with constanvoltage and welding speed were 24 V and 25 inchi/minutes respectivelly. Collected data were evaluated use of analysis ofvariance and regresion analysis.The results of investigation show that; electric current has a significant effect towardstrength of aluminium 1100 welding junction; the characteristic trend to represent relationship between electric current andstrength of aluminium 1100 welding junction is polynomial orde 2; the highest strength of aluminium 1100 welding junctionwas obtained by use of electric current 180 A there was 11,900 kgf/mm2.
Keywords: MIG, Strength of welding junction, Analysis of variance, Regresion analysis